A CO2 utilization approach towards the synthesis of terephthalic acid via a catalytic double carboxylation. (March 2018) - Thompson, Samuel J.; Gohndrone, Thomas R.; Lail, Marty
Graphical abstract: Abstract: A catalytic double carboxylation of a bisboronate ester benzene was disclosed to synthesize terephthalic acid under a CO2 utilization approach. The double carboxylation was accomplished with several other bisboronate ester arenes to provide support for this being a general transformation. The double carboxylation was conducted on a gram scale to provide terephthalic acid in 90% yield.